Few-layer MoS2 embedded in N-doped carbon fibers with interconnected macropores for ultrafast sodium storage. (30th October 2020) - Cheng, Ao; Zhang, Haiyan; Zhong, Weihao; Li, Zhaopeng; Cheng, Dejian; Lin, Yingxi; Tang, Yudie; Shao, Huaiyu; Li, Zhenghui
Abstract: Sodium-ion battery has been considered as one of the most promising next-generation rechargeable energy storage devices. However, it remains a great challenge to exploit suitable electrode materials for sodium storage owing to relatively large radius of Na + . In this study, a novel 1D fiber-like electrode material integrating few-layer MoS2, ultrathin carbon continuous framework, doped N atoms and well-defined 3D connected macropores is developed by electrospinning (denoted as MoS2 /NCF-MP). When used as anode in sodium ion battery, its unique structural hierarchy is able to maximumly diminish the solid-state diffusion length, lower electrochemical resistance, accelerate Na + transfer from bulk to electrode, and relieve the volume variation during sodiation/desodiation process, thus displays highly reversible capacity, long-term durability, along with ultrafast sodium storage capability. The stable reversible capacity of MoS2 /NCF-MP reaches 480 mAh g −1  at 0.1 A g −1 after 100 cycles, and undergoes a long cycling life of 300 cycles at 1 A g −1, no visible capacity degradation is observed. More importantly, even under a very high current density of 30 A g −1, the MoS2 /NCF-MP can deliver a commendable capacity of 217 mAh g −1, which means the charge/discharge step can be completed within a very short time of 26 s. Graphical abstract: Image 1